Recent advances in multimodality imaging of the tricuspid valve. (2nd November 2021) - Caravita, Sergio; Figliozzi, Stefano; Florescu, Diana-Ruxandra; Volpato, Valentina; Oliverio, Giorgio; Tomaselli, Michele; Torlasco, Camilla; Muscogiuri, Giuseppe; Cernigliaro, Franco; Parati, Gianfranco; Badano, Luigi; Muraru, Denisa
ABSTRACT: Introduction: The tricuspid valve (TV) and the right heart chambers are complex three-dimensional structures that are difficult to assess using tomographic imaging techniques. The progressive aging of the general population and the advancements in treating left-sided heart diseases by transcatheter procedures have contributed to the tricuspid regurgitation (TR) becoming a major public health problem associated with progression to refractory heart failure and poor outcome. Recent advances in multimodality cardiac imaging allow a better understanding of the pathophysiology of TR that may translate in better management of patients. Areas covered: Three-dimensional echocardiography, cardiac magnetic resonance, and computed tomography provide complementary information to i . assess the TV complex; ii . identify the etiology and the mechanisms of TR; iii . evaluate its severity and hemodynamic consequences; iv . explore the remodeling of the right heart chambers; and v . properly plan, guide, and monitor the transcatheter interventions aimed to reduce the severity of TR. Expert opinion: We need thorough understanding of both the TV and the right heart chamber geometry and function to understand the pathophysiology of TR. The integrated use of multimodality cardiac imaging is pivotal to assess patients with TR and to identify tailored and timely treatment of TR in properly selected patients.